Penurunan Kecemasan Ibu dengan Mengikuti Kelas Ibu Hamil Prenatal Yoga - Indah Nurfazriah; Innama Sakinah (Faletehan Health Journal, 2021)
The issue of maternal mortality is a serious problem faced by the Ministry of Health. Many maternal deaths occurred in the intra-natal and post-natal period. This could be due to unpreparedness of the mothers in facing the labor process so that information related to pregnancy, childbirth and postnatal period was not fully and up to date known by them. Information related to pregnancy, childbirth and postpartum can be obtained through antenatal visits, especially by the implementation of antenatal classes. The purpose of this study was to determine the anxiety differences of third trimester pregnant mothers in facing childbirth before and after participating prenatal yoga classes at Ciruas Public Health Center, Serang Regency in 2018. The method used in this study was pre-experimental research design one-group pre-test and post-test. The results showed most participants were the age group 20-35 years, namely 21 people (70%) and the most maternal parity is multigravidas, namely 20 people (67%). The level of maternal anxiety in facing childbirth were mostly moderate as many as 25 pregnant mothers (83.3%), and after participating prenatal yoga classes, most of the mothers had mild anxiety, namely 27 pregnant women (90%). To conclude, prenatal yoga classes are effective on reducing the incidence of maternal anxiety in facing childbirth.